The Existence of Female Ulama in the Election of Religious Decisions of Rural Communities in Sedan,Rembang - Moch. Rusli; Ikhda Khullatil Mardliyah (Journal of Islamic Studies and Education, 2023)
Sedan is one of the sub-districts that has the highest level of religious adherence in Rembang Regency and has fanaticism towards female ulema. This study discusses the role of female ulema in influencing rural communities. This study aims to discuss the existence of female ulema, especially in the village in influencing the community in deciding their religious actions because of the authority that these female ulema has. The method used in this research is a qualitative approach. The analysis and data collection process was carried out by observation and interviews with informants whose backgrounds were female ulema who preached, young women, middle-aged women, all of whom came from rural areas. The activity started with the preaching activities of female ulema, efforts to approach rural communities, and paying attention to washatiyah through their preaching methods. From this research it is known that in the rural area, female ulema have an important influence as evidenced by the high number of rural people who come every preaching of female ulema, people often turn to female ulema in determining their main decisions related to religious matters, so that women ulema are very entrusted with rural community activities. This has a positive impact on the community with the ease with which the community makes religious decisions because of the existence and authority of female ulema in the midst of rural communities.